Effect of administration of ajwa date extract on renal histopathological changes in meloxicam induced in rats - Abdul Halim, Musdalifah; Arsyad, M Aryadi; Dwi Kesuma Sari; Sartini Natsir; Muhammad Husni Cangara; Yulia Yusrini Djabir (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
Objective: This study aimed to examine the nephroprotector effect of ajwa date extract on the kidneys of white rats induced by meloxicam. Methods: 25 male (Rattus norvegicus) rats weighing 200-300 g were divided into 5 groups (n = 5), namely group 1 healthy control without meloxicam and ajwa date extract, group 2 negative control with meloxicam 30mg/kgBB without ajwa dates, group 4 with ajwa date extract 150mg/kgBW and meloxicam 30mg/kgBW, and group 5 with ajwa date extract 300mg/kgBW and meloxicam 30mg/kgBW. The treatment was given for 14 days, on the 15th day a necropsy was performed to take kidney organs for microscopic evaluation or histipathological examination. Results: Meloxicam at a dose of 30mg/kgBW caused damage to the kidneys with observations of glomerular hemorrhage, tubular necrosis, hydropic degeneration and narrowing of the tubular lumen as well as narrowing of the capsular space with an average degree of damage reaching 75% while ajwa date extract doses of 150 and 300mg/kgBW has a nephroprotector effect against meloxicam induction. Conclusion: Ajwa date extract doses of 150 and 300mg/kgBW had a nephroprotector effect on meloxicam induction.